A Multidisciplinary Team Approach Is Highly Effective in the Management of Nondiagnostic Bone Tumour Biopsies: A 10-Year Retrospective Review at a Specialist Sarcoma Unit. (28th March 2022) - Osman, Khabab; Hussain, Shakir; Downes, Frederick; Sumathi, Vaiyapuri; Botchu, Rajesh; Evans, Scott
Abstract : Nondiagnostic (ND) biopsies are frequently encountered during the investigation of bone tumours and can lead to treatment delay. We performed a retrospective review of all ND bone tumour biopsies discussed at our regional MDT meeting between 2004 and 2014 with the aim of establishing the incidence of ND biopsies, identifying any factors that could predict the requirement for repeat biopsies, and evaluating the effectiveness of multidisciplinary team (MDT) decisions. We identified 98 ND out of 4949 biopsies. Diagnostic yield (DY) was 98%, 76%, and 40% for the first, second, and third successive biopsy, respectively. With an MDT approach utilising radiological and clinical information, the diagnostic success rate achieved was 99%, 85%, and 80% for the first, second, and third biopsies, respectively. Although a repeat biopsy was only performed in 34% of cases, there were no patients originally diagnosed with a benign lesion that re-presented with the same lesion subsequently being malignant throughout the study period. Malignant primary bone tumours (p < 0.01 ) and malignant secondary tumours (p = 0.02 ) were more likely to undergo repeat biopsy compared to benign and infective lesions. Upper limb (p = 0.04 ) and lower limb (p = 0.03 ) were more likely than pelvic and spinal tumours to undergo a repeat biopsy. Tumours of haematological origin frequently required multiple biopsies. Our study demonstrated that a specialist MDT approach leads to high diagnostic rates and is a safe and effective method of preventing unnecessary, repeat biopsies where the initial biopsy is ND.